Η αγορά του θαλάσσιου τουρισμού στην Ελλάδα: Η μελέτη περίπτωσης των ταχυπλόων πολυεστερικών και φουσκωτών σκαφών - Γασπαράτου, Νικολέτα (2017)
Sea tourism is a form of alternative tourism that is widespread since it includes a range of activities related to the sea. This paper will examine the sea tourism market in Greece, focusing on high-speed polyester and inflatable boats. The rapid growth that has taken place in recent years in the field of sea tourism and the prospects it offers for the future of our country's tourism development have prompted me to deal with this subject in this paper. The tourist product of Greece "Sun and Sea" is already in its maturity stage. The need for diversification and enrichment has been highlighted by competent tourism operators and not only. This is why, in this paper, maritime tourism is initially presented. There is a conceptual approach followed by maritime tourism both at international level and in Greece. Next, the various types of sea tourism, sea recreation, and the various categories of recreational craft are presented. Also, the institutional framework of the vessels in Greece is presented. Specifically, in the first instance, some basic definitions are presented, and then the general legislative framework surrounding the vessels. Subsequently, the chartering procedure of a vessel, with its charter charter, the general tax framework, the immobilisation fee imposed by the Law and the registration procedure in the Registry are presented. Lastly, special attention is given to the presentation of the vessel's logging and lightening process in Greece.